Application of low-temperature-phase Y2SiO5 nickel-based catalyst for hydrogen production through acetic acid reforming

The low-temperature phase Y2SiO5-supported Ni-based catalyst prepared by using the sol-gel method during the acetic acid autothermal reforming process, the problem of deactivation of traditional catalysts under high temperature and oxidation atmosphere was solved, and the thermal stability and efficient hydrogen yield of the catalyst were achieved.

CN119819311APending Publication Date: 2025-04-15CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510073097.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the acetic acid autothermal reforming process, the Ni-based catalyst is deactivated due to oxidation atmosphere and high temperature, and is prone to carbon accumulation and sintering, resulting in a decrease in catalytic activity and stability.

Method used

The sol-gel method was used to prepare Ni-based catalysts supported by low-temperature phase Y2SiO5. The monoclinic crystal structure and good thermal stability of the low-temperature phase Y2SiO5 were used to form a large number of active O2-ions, promote the gasification of intermediate species, and inhibit agglomeration and sintering through uniformly distributed Ni0.

Benefits of technology

The thermal stability, resistance to carbon deposits and sintering capacity of the catalyst is improved, and efficient acetic acid conversion and hydrogen yield are achieved, and the catalyst maintains good activity and selectivity in the reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819311A_ABST
    Figure CN119819311A_ABST
Patent Text Reader

Abstract

The invention relates to a low-temperature phase Y2SiO5 nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid. Aiming at the problem of inactivation of the existing catalyst in the autothermal reforming process of acetic acid, a sol-gel method is adopted, Ni is taken as an active component, Y and Si are introduced to form a low-temperature phase Y2SiO5 loaded nickel-based catalyst, and the carbon deposition resistance, the sintering resistance and the hydrogen yield of the catalyst are improved. The chemical composition of the catalyst is (NiO) a (YO1.5) b (SiO2) c, a ranges from 0.40 to 0.48, b ranges from 1.86 to 2.12, and c ranges from 0.88 to 1.14.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a low temperature phase Y 2 SiO 5 The invention discloses an application of autothermal reforming of acetic acid to produce hydrogen using a nickel-based catalyst, belonging to the field of autothermal reforming of acetic acid to produce hydrogen. Background Art

[0002] Hydrogen has attracted wide attention as a sustainable and clean energy source. Biomass oil is obtained by pyrolysis of biomass, from which a large amount of acetic acid can be separated, which can be used as a cheap raw material for large-scale production of hydrogen.

[0003] Traditionally, acetic acid can be used to produce hydrogen through steam reforming, i.e. CH 3 COOH+2H 2 O→2CO 2 +4H 2 (ΔH = +131.4 kJ / mol), which is a strongly endothermic reaction with high heat exchange requirements; while partial oxidation reforming only introduces oxygen or air, and its hydrogen yield is low. Compared with the above two reforming hydrogen production methods, autothermal reforming adjusts the reaction degree by changing the ratio of oxygen to reactants, thereby achieving thermal balance in the reaction system, that is, CH 3 COOH+xO 2 +yH 2 O→aCO+bCO 2 +cH 2 (ΔH=0 kJ / mol); This method uses acetic acid, water, air or oxygen as raw materials, and combines the advantages of steam reforming and partial oxidation reforming. It can not only maintain a high hydrogen yield, but also reduce dependence on external heat sources, with significant advantages.

[0004] The process of hydrogen production by autothermal reforming of acetic acid is complex, and the reaction path is affected by many factors. How to choose a suitable catalyst is the key to the process. Among the many transition metals, Ni-based catalysts have excellent activation ability for chemical bonds such as CC, CH, CO, and OH, which can effectively improve the conversion rate of acetic acid and are expected to be used in the autothermal reforming reaction of acetic acid.

[0005] However, during the autothermal reforming of acetic acid, the oxygen in the feed gas is consumed in large quantities at the front end of the bed, and the temperature can reach 1000°C, causing the Ni-based catalyst at the front end of the bed to lose its activity due to agglomeration and sintering. At the same time, the oxidizing atmosphere during the autothermal reforming process will also cause Ni 0 In addition, due to the dehydrogenation and dehydroxylation of acetic acid, CH 3 COO*、CH 3 CO* and CH 3* and other intermediate species, and then generate C*; a large amount of C* accumulates on the surface of Ni-based catalysts to form carbon deposits, which reduces the activity and stability of the catalyst.

[0006] In order to solve the above problems, the present invention has created a low temperature phase Y 2 SiO 5 Supported Ni-based catalysts are used in the acetic acid autothermal reforming process: Based on the requirements for the controlled conversion of acetic acid in the acetic acid autothermal reforming process, a low-temperature phase Y with a monoclinic crystal structure is introduced. 2 SiO 5 As a carrier. Due to the different synthesis temperatures, Y 2 SiO 5 It has two different crystal structures, namely high temperature phase and low temperature phase. 3+ Occupies two different positions, Y 3+ The coordination numbers with oxygen are 6 and 7 respectively; compared with the high temperature phase, the low temperature phase Y 2 SiO 5 The preparation temperature is low, and the structure contains two Y 3+ , respectively coordinated with 7 O and 9 O to form two distorted octahedral structures, generating a large amount of lattice oxygen transferred to the reaction interface, forming a large amount of active O 2- The ions promote the gasification of intermediate species such as *CHx (x=0-3) produced during the conversion of acetic acid, and improve the catalyst's ability to resist carbon deposition.

[0007] At the same time, the low temperature phase Y 2 SiO 5 It has good thermal stability, effectively improving the structural stability of the yttrium silicate carrier during the reaction process, and providing a stable reaction interface for acetic acid conversion; at the same time, Ni 0 Uniform distribution can effectively inhibit Ni particle agglomeration and carrier sintering, and improve its thermal stability.

[0008] Therefore, the innovation of the catalyst of the present invention in the catalyst structure and reaction pathway improves the thermal stability, anti-coking and anti-sintering capabilities of the catalyst in the acetic acid autothermal reforming reaction; the activity test results of the catalyst applied to the acetic acid autothermal reforming reaction also show that the catalyst of the present invention has good activity, selectivity and stability. Summary of the invention

[0009] The present invention creatively prepares low temperature phase Y by sol-gel method. 2 SiO 5The nickel-based catalyst solves the problems of poor stability, easy carbon deposition, and easy sintering in the autothermal reforming process of acetic acid with conventional catalysts. When the catalyst of the present invention is used in the autothermal reforming of acetic acid to produce hydrogen, the acetic acid conversion rate is close to 100% at a reaction temperature of 650°C, and the hydrogen yield can be stabilized at 2.71 mol-H 2 / mol-HAc. The results of activity test and phase analysis of the catalyst confirmed that the catalyst has the characteristics of anti-coking, sintering resistance and stable activity.

[0010] Technical solution of the present invention:

[0011] In view of the characteristics of acetic acid autothermal reforming, the present invention uses a sol-gel method to prepare a low-temperature phase Y 2 SiO 5 Nickel-based catalyst. The chemical composition of the catalyst of the present invention is (NiO) a (YO 1.5 ) b (SiO 2 ) c , wherein a is 0.40-0.48, b is 1.86-2.12, and c is 0.88-1.14; the composition in terms of weight percentage of oxides is: nickel oxide is 9.5%-10.5%, yttrium oxide is 70.3%-73.5%, silicon dioxide is 16.5%-20.1%, and the sum of the weight percentages of each component is 100%.

[0012] The specific preparation method steps are as follows:

[0013] 1) According to the ratio of each component of the catalyst chemical composition (NiO) a (YO 1.5 ) b (SiO 2 ) c , wherein a is 0.40-0.48, b is 1.86-2.12, and c is 0.88-1.14, yttrium nitrate hexahydrate is weighed and dissolved in anhydrous ethanol solution, and stirred in a constant temperature water bath at 70°C for 1 hour to obtain solution #1;

[0014] 2) Weigh a certain amount of tetraethyl orthosilicate, add a certain amount of distilled water and a mixed solution of anhydrous ethanol (the volume ratio of anhydrous ethanol to distilled water is 3:1), stir at room temperature for 1 hour, add solution #1, and then add a certain amount of hydrochloric acid (HCl mass fraction 36%-38%), and stir to obtain a mixed solution #2;

[0015] 3) Weigh a certain amount of nickel nitrate hexahydrate, add it to mixed solution #2, stir at 50°C until a colloid is formed, let it stand at room temperature for 15 hours, and then dry it in an oven at 80°C for 24 hours;

[0016] 4) The dried sample was placed in a tube furnace, heated from room temperature to 950°C at a rate of 5°C / min, and calcined in air for 4 h. The typical crystal structure is shown in the attached figure. Figure 1 As shown in the XRD pattern, a low temperature phase Y 2 SiO 5 The catalyst with the nickel active component supported on the crystalline phase has a mesoporous structure, and its typical BJH pore size distribution is as shown in the attached Figure 2 As shown;

[0017] 5) The catalyst of the present invention is 2 After reduction treatment at 600-800°C in an atmosphere, the mixture is purged with nitrogen atmosphere and an autothermal reforming reaction is carried out through a catalyst bed with a mixed gas having a molar ratio of acetic acid / water / oxygen = 1 / (1.3-5.0) / (0.21-0.35) at a reaction temperature of 500-800°C and normal pressure.

[0018] Beneficial effects of the present invention:

[0019] 1) The present invention uses a sol-gel method to obtain a low-temperature phase Y with a mesoporous structure 2 SiO 5 The nickel-based catalyst forms a Ni-Y-Si-O active center. The activity test results of acetic acid autothermal reforming show that the acetic acid conversion rate is close to 100%, and the hydrogen yield can be stabilized at 2.71 mol-H 2 / mol-HAc, and can effectively inhibit the ketonization reaction and the production of by-products such as acetone, ketene and methane. It has the characteristics of sintering resistance, carbon deposition resistance, stable activity and high hydrogen yield.

[0020] 2) In the low temperature phase Y constructed by the present invention 2 SiO 5 In the carrier structure, its crystal phase belongs to the monoclinic biaxial system, with p2 1 / c space group monoclinic structure, its unit cell parameters a = 9.014 Å, b = 6.928 Å, c = 6.643 Å, crystal plane angle β = 102.68°; the low temperature phase Y 2 SiO 5 Si in the structure 4+ Located in [SiO 4 ] tetrahedral center, the oxide network formed by Si-O bonds provides high temperature stability; at the same time, the two Y 3+ The 7 oxygen atoms and the 9 oxygen atoms coordinate with each other to form two distorted octahedral structures, generating a large amount of active lattice oxygen that transfers to the reaction interface. 2-The ions promote the gasification of intermediate species such as *CHx (x=0-3) formed during the conversion of acetic acid; at the same time, the basic rare earth element Y increases the overall basicity of the catalyst on the Ni-Y-Si-O active site, and the Lewis basic site formed reacts with CO 2 The molecules interact electrostatically, promoting CO 2 The conversion of C* and the generation of active oxygen (O*) promote the gasification of C* and improve the catalyst's anti-coking ability.

[0021] 3) Low temperature phase Y constructed by the present invention 2 SiO 5 The nickel-based catalyst consists of edge-sharing 8- or 9-coordinated yttrium ion polyhedra and smaller [SiO4] tetrahedra. The silicon ions are connected to the yttrium sites through edge sharing, while the edge-sharing tetrahedra are distorted in structure, targeting the reactant molecule CH in the autothermal reforming of acetic acid. 3 COOH、O 2 and H 2 O activation provides more adsorption sites, and the active component Ni metal particles are dispersed on the Ni / Y silicate skeleton. 2 SiO 5 The catalyst formed a Ni-Y-Si-O active center, which promoted the CH 3 COO*、CH 3 The formation and transformation of intermediate species such as CO* to obtain H 2 And other target products.

[0022] 4) The present invention constructs a new catalyst with a mesoporous structure, which induces the adsorption of acetic acid, water, and oxygen molecules in the reactants in the pores and H 2 ,CO,CO 2 The transport and diffusion of products such as Ni 0 The distribution in the pores effectively inhibits the Ni 0 agglomeration and improve the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : X-ray diffraction spectrum of the catalyst of the present invention after calcination;

[0024] Figure 2 : BJH pore size distribution diagram of the catalyst of the present invention. DETAILED DESCRIPTION

[0025] Reference example one

[0026] Weigh 12.470 g of tetraethyl orthosilicate, add 30 mL of distilled water and 10 mL of anhydrous ethanol, and stir at room temperature for 1 h to form solution 1#; weigh 1.568 g of Ni(NO3 ) 2 6H 2 O was added to solution 1#, stirred, and then 1 mL of hydrochloric acid (HCl mass fraction 36%-38%) was added, stirred until a colloid was formed, and allowed to stand at room temperature for 15 h; dried in an 80°C drying oven for 24 h; the dried and foamed sample was crushed, heated to 950°C at a heating rate of 5 °C / min, and calcined for 4 h to obtain the CDUT-NS catalyst, which was supported on SiO 2 The nickel-based catalyst is composed of 10.0% nickel oxide and 90.0% silicon dioxide in terms of weight percentage of oxides.

[0027] The activity evaluation of acetic acid autothermal reforming reaction was carried out in a continuous flow fixed bed reactor. The catalyst was ground and tableted, crushed, and sieved to obtain 20-40 mesh particles, which were loaded into the reactor and heated at 600-800°C and 30 mL / min of H 2 The mixture was reduced in a 10% mol / l atmosphere for 1 h, and then the acetic acid-water mixture was injected into a vaporizer by a high-pressure constant flow pump for vaporization, mixed with oxygen, and nitrogen was used as the internal standard gas to form a molar composition of CH 3 COOH / H 2 O / O 2 =1 / (1.3-5.0) / (0.21-0.35) of reaction raw gas, and the raw gas is passed into the reaction bed to carry out acetic acid autothermal reforming reaction, the reaction conditions are 500-800°C, normal pressure, and space velocity 20000-60000mL / (g-catalyst·h), and the reaction is analyzed online by gas chromatograph.

[0028] The activity of the CDUT-NS catalyst was investigated by autothermal reforming of acetic acid under the following reaction conditions: atmospheric pressure, space velocity of 50000 mL / (g-catalyst h), reaction temperature of 700 °C, feed ratio of CH 3 COOH / H 2 O / O 2 =1 / 4.0 / 0.28, the acetic acid conversion rate of the catalyst was 99.8%, and the hydrogen yield increased from 1.16 mol-H 2 / mol-HAc decreased to 0.189mol-H 2 / mol-HAc, CO 2 The selectivity is about 8.22%, CO selectivity is about 58%, CH 4 The selectivity approaches about 26.1%, and the selectivity of by-product acetone increases to about 1%. 2-TPR and other characterization results show that the catalyst has poor stability during the autothermal reforming of acetic acid and produces a large number of by-products. The methanation reaction is not effectively inhibited, and sintering, carbon deposition and partial oxidation occur, resulting in low selectivity.

[0029] Embodiment 1

[0030] Weigh 9.629 g of yttrium nitrate hexahydrate, add 30 mL of anhydrous ethanol, stir in a constant temperature water bath at 70°C for 1 h to prepare solution #1; weigh 2.619 g of tetraethyl orthosilicate, add 30 mL of distilled water and a mixed solution with 10 mL of anhydrous ethanol, stir at room temperature for 1 h, add solution #1, and then add 1 mL of hydrochloric acid (HCl mass fraction 36%-38%), stir to obtain mixed solution #2; weigh 1.572 g of Ni(NO 3 ) 2 6H 2 O, added to the mixed solution #2, stirred at 50°C until a colloid was formed, and allowed to stand at room temperature for 15h; placed in an 80°C oven for drying for 24h; the dried sample was placed in a tube furnace, heated from room temperature to 950°C at a rate of 5°C / min, and calcined in air for 4h. Its typical structure is shown in the attached figure. Figure 1 As shown, a low-temperature phase of yttrium silicate and nickel oxide phases are formed, and the active component Ni is dispersed in the low-temperature phase Y 2 SiO 5 Ni / Y on the skeleton 2 SiO 5 The catalyst formed a Ni-Y-Si-O active center, namely the CDUT-NYS catalyst, and a mesoporous structure was obtained, and its pore size distribution is shown in the attached Figure 2 As shown. The catalyst molar composition is (NiO) 0.43 (YO 1.5 ) 2 (SiO 2 ) 1 The weight percentage composition of the oxides is: 10.0% nickel oxide, 71.2% yttrium oxide, and 18.8% silicon dioxide.

[0031] The activity of CDUT-NYS catalyst was investigated by autothermal reforming of acetic acid under the following reaction conditions: atmospheric pressure, space velocity of 50000 mL / (g-catalyst h), reaction temperature of 700 °C, feed ratio of CH 3 COOH / H 2 O / O 2 =1 / 4.0 / 0.28, and the reaction time was 10 h, the acetic acid conversion rate of the catalyst was about 100%, and the hydrogen yield was stable at 2.71 mol-H 2 / mol-HAc, CO 2The selectivity is about 65.3%, the CO selectivity is about 34.6%, and there are only trace byproducts acetone and methane. The catalytic activity is stable during the reaction. The CDUT-NYS catalyst was characterized by BET and XRD, and it was found that the catalyst formed a monoclinic system with a space group of P2 1 / c Low temperature phase Y 2 SiO 5 , with a specific surface area of ​​11.3m 2 / g, pore volume is 0.109cm 3 / g, and an average pore size of 17.4nm. From the reaction and characterization results, it can be seen that the low temperature phase Y 2 SiO 5 Nickel-based catalysts have the advantages of resistance to carbon deposition, resistance to sintering, stable structure and high hydrogen production rate.

Claims

1. Application of low temperature phase Y2SiO5 nickel-based catalyst in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: After the catalyst is reduced in H2 atmosphere at 600-800°C for 1h, a mixed gas with a molar ratio of CH3COOH / H2O / O2=1 / (1.3-5.0) / (0.21-0.35) is introduced through the catalyst bed to carry out acetic acid autothermal reforming reaction at a reaction temperature of 500-800°C; the catalyst is prepared by the following method: according to the chemical composition, yttrium nitrate hexahydrate is weighed and dissolved in anhydrous ethanol solution, and stirred in a constant temperature water bath at 70°C for 1h to obtain solution #1; a certain amount of tetraethyl orthosilicate is weighed, a certain amount of distilled water and a mixed solution with anhydrous ethanol (the volume ratio of anhydrous ethanol to distilled water is 3:1) are added, and stirred at room temperature 1h, add solution #1, and then add a certain amount of hydrochloric acid (HCl mass fraction 36%-38%), stir to obtain mixed solution #2; weigh a certain amount of nickel nitrate hexahydrate, add it to mixed solution #2, stir at a temperature of 50°C until a colloid is formed, let it stand at room temperature for 15h, and then dry it in an oven at 80°C for 24h; put the dried sample into a tubular furnace, heat it from room temperature to 950°C at a rate of 5°C / min, and calcine it in air for 4h to obtain a Ni / Y2SiO5 nickel-based catalyst in which the active component is loaded on the low-temperature phase Y2SiO5 skeleton, and a Ni-Y-Si-O active center is formed; the chemical composition of the catalyst of the present invention is (NiO) a (YO 1.5 ) b (SiO2) c , wherein a is 0.40-0.48, b is 1.86-2.12, and c is 0.88-1.14; the weight percentage composition calculated as oxides is: nickel oxide is 9.5%-10.5%, yttrium oxide is 70.3%-73.5%, silicon dioxide is 16.5%-20.1%, and the sum of the weight percentages of each component is 100%.

2. The use of the low temperature phase Y2SiO5 nickel-based catalyst according to claim 1 in the process of producing hydrogen by autothermal reforming of acetic acid, characterized in that: The catalyst is composed of 10.0% nickel oxide, 71.2% yttrium oxide and 18.8% silicon dioxide in terms of weight percentage of oxides.